Enalapril therapy and thrombotic or inflammatory disturbances in essential arterial hypertension - O. M. Moiseeva; O. A. Berkovich; S. V. Villevalde; I. V. Emelyanov (Российский кардиологический журнал, 2005)
The authors studied enalapril therapy perspectives for correction of factors related to arterial thrombosis and inflammatory disturbances development in vascular wall among patients with essential arterial hypertension (EAR). The study included 21 males with Stage II ЕАН, and 17 healthy individuals. Echocardiography, blood rheology parameters, white blood cell functional activity, plasma levels of von Willebrand factor and ICAM, were measured. Next examination was performed after 24-week enalapril therapy (10-40 mg/d). Enalapril therapy was associated with improved blood rheology, decreased white blood cell functional activity and plasma levels of von Willebrand and ICAM, as well as left ventricular hypertrophy (LVH) regression. In EAH patients, long-term enalapril therapy resulted in LVH regression, reduced thrombo- and atherogenesis.